ANALISIS KETERLAKSANAAN PROGRAM REMEDIAL MATA PELAJARAN IPA SMP BERBASIS KURIKULUM 2013 DI KOTA MAKASSAR - Nuraeni; Safira, Ifa (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The objectives of this research are to find out the preparation, implementation and outcomes of Remedial program of IPA Natural Science Subject of Secondary Schools in Makassar city. Sample of this research were 24 Science teachers selected from 8 Secondary Schools with A certification in Makassar city. This is a descriptive research which employed an ex-post facto method on remedial program implementation of Science teacher of secondary schools based on curriculum 2013. The Instrument used to collect data were by observation sheet, collection were by observation, interview guideline, and camera for documentation. Technique of data collection were by observation, interview, and documentation.The instrument was tested by the 2 experts who validated and analyzed the instrument by items validation through score number. The analysis was conducted by data reduction, data display, and drawing conclusion. The result indicates that the Science teachers is on the fair category ( 77,00%). In conducting the remedial program preparation.The teachers have conducted the remedial program by organizing the lesson plan by preparing the regular material, remedial material, and enrichment material according to Regulation of Education and Cultur Ministry No 103 year 2014. The implementation of remedial program by Science teachers is on thr fair category (73,27%). Teachers have implemented the remedial program, even though the implementation was not fully meet the technical instruction of the program. The outcomes of remedial program implementation of Science subject is on the low category (63,75%). Decresing of remedial program result caused by preparing and applicated remedial program doing by teacher on the fair category, and given effect to result of remedial program. Keywords: Remedial Program, Curriculum 2013, Minimum Mastery Criteria